Retrospective study on patient comfort and post-operative condition associated with intravenous sedation versus general anesthesia for third molar extraction in ambulatory surgery in a state hospital - Légroz Eloise; Bratiloveanu Petre Lupu; Varazzani Andrea (Journal of Oral Medicine and Oral Surgery)
Objectives: Third molar extraction requires local or general anesthesia. In public hospitals, general anaesthesia is frequently used to perform the most complex extractions and to accommodate patients' wishes. However, the choice of general anesthesia is at the discretion of the care center. Intravenous sedation is also an option. We suggest that comfort and post-operative condition are better in patients undergoing sedation rather than general anesthesia. This study aimed to evaluate the comfort and post-operative condition after third molar extraction in an 18–50-year-old ambulatory surgical population in a state hospital. Method and materials: In the stomatology and maxillofacial surgery department of Roanne Hospital, two anesthetic protocols are used for third-molar extraction. We retrospectively collected 47 patients who underwent third molar extraction between 1st July 2022 and 31st December 2022. Results were collected by questionnaires and data were retrospectively retrieved from medical records. Results: Twenty patients underwent a general anesthesia and twenty-seven underwent intravenous sedation. The study found no difference for the pain level (p < 0.62) between the two anesthesia techniques. The comparison of the approaches indicated that intravenous sedation required a shorter duration of anesthesia (p < 0.0001) and a shorter time in the recovery room (p < 0.0001). Conclusion: This study indicates the feasibility and the effectiveness of intravenous sedation for patients undergoing third molar extraction in a state hospital. As other studies in the literature that have shown greater satisfaction and better recovery in patients undergoing intravenous sedation compared with general anesthesia.